Naturalistic Inquiry and Reserach for Children - Valentina Mazzoni (Encyclopaideia, 2016)
The present article aims at discussing the connection between two research approaches: the naturalistic inquiry and the “research for children” approach, developed by Luigina Mortari. The thesis that will be developed is that the “research for children” approach is particularly coherent with the naturalistic inquiry, when researchers study children and teachers in school settings. The main principle of the naturalistic inquiry is to realize research in natural settings and study phenomena as they unfold naturally. Today many researches are realized in school settings, but simply doing studies in schools does not mean developing a naturalistic inquiry. Taking as example a research on virtues that the author has developed with primary school children in their schools following the research for children approach, the article will outlines some important elements to take into consideration to develop a naturalistic inquiry.